Differentiation of human pluripotent stem cells into β-cells: Potential and challenges. Issue 6 (December 2015) - Quiskamp, Nina; Bruin, Jennifer E.; Kieffer, Timothy J.
Abstract : Human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) hold great potential as the basis for cell-based therapies of degenerative diseases, including diabetes. Current insulin-based therapies for diabetes do not prevent hyperglycaemia or the associated long-term organ damage. While transplantation of pancreatic islets can achieve insulin independence and improved glycemic control, it is limited by donor tissue scarcity, challenges of purifying islets from the pancreas, and the need for immunosuppression to prevent rejection of transplants. Large-scale production of β-cells from stem cells is a promising alternative. Recent years have seen considerable progress in the optimization of in vitro differentiation protocols to direct hESCs/iPSCs into mature insulin-secreting β-cells and clinical trials are now under way to test the safety and efficiency of hESC-derived pancreatic progenitor cells in patients with type 1 diabetes. Here, we discuss key milestones leading up to these trials in addition to recent developments and challenges for hESC/iPSC-based diabetes therapies and disease modeling.